Why Health Matters to Justice: A Capability Theory Perspective - Nielsen, Lasse (Ethical theory and moral practice, 2015)
The capability approach, originated by Amartya Sen is among the most comprehensive and influential accounts of justice that applies to issues of health and health care. However, although health is always presumed as an important capability in Sens works, he never manages to fully explain why health is distinctively valuable. This paper provides an explanation. It does this by firstly laying out the general capability-based argument for health justice. It then discusses two recent attempts to justify why health is distinctively valuable from within a capability framework - these are Sridhar Venkatapurams conception of health as the central human meta-capability and, respectively, Norman Daniels embrace of the capability metric in his use of Rawls principle of fair equality of opportunity. The paper argues that none of these accounts succeed in providing a plausible justification of the value of health. Finally, the paper suggests an alternative more complex justification, closely tied to different but central element of the capability view, that captures the core intuitions of both Venkatapuram and Daniels accounts but without being vulnerable to the objections raised against each of them. This, the paper concludes, provides a promising ground on which the capability view on health justice should be founded.